IMPLEMENTASI ALGORITMA DIJKSTRA DALAM MENENTUKAN RUTE TERPENDEK BIS TRANSJAKARTA DALAM MENGUNJUNGI 5 DESTINASI WISATA POPULER DI JAKARTA - TAPOBALI, PATRICIA JOSEPHINE BAREK BABA; KRISNAMURTI, CYRENIA NOVELLA (E-Jurnal Matematika; Vol 9 No 4 (2020)DO - 10.24843/MTK.2020.v09.i04.p307, 2020)
This study shows the Dijkstra Algorithm process in determining the shortest Transjakarta bus route connecting 5 popular tourist destinations in Jakarta, namely; Ragunan Wildlife Park, Beautiful Indonesia Miniature Park, National Monument, Old Town, and Ancol Dreamland. Based on the analysis of the data obtained by the 5 shortest routes in visiting 5 popular tourist destinations in Jakarta with the initial position is a different tourist destination, namely; (1) TMII ? Monas ? City ? Ancol ? Ragunan with the length of the Transjakarta bus lane is 57.6 kilometers. (2) Ragunan ? Monas ? City ? Ancol ? TMII with the length of the Transjakarta bus lane is 47.38 kilometers. (3) Monas ? City ? Ancol ? Ragunan ? TMII with the length of the Transjakarta bus lane is 53.86 kilometers. (4) City ? Ancol ? Monas ? Ragunan ? TMII with the length of the Transjakarta bus lane is 49.46 kilometers. (5) Ancol ? City ? Monas ? Ragunan ? TMII with the length of the Transjakarta bus lane is 46.41 kilometers.